Secondary metabolites and transcriptomic analysis of novel pulcherrimin producer Metschnikowia persimmonesis KIOM G15050: A potent and safe food biocontrol agent - Rahmat, Endang; Yu, Jae Sik; Lee, Bum Soo; Lee, Jiyoung; Ban, Yeongjun; Yim, Nam-Hui; Park, Jeong Hwan; Kang, Chang Ho; Kim, Ki Hyun; Kang, Youngmin (Heliyon, 2024)
Metschnikowia persimmonesis, a novel endophytic yeast strain isolated from Diospyros kaki calyx, possesses strong antimicrobial activity. We investigated its potential use as an environmentally safe food biocontrol agent through genomics, transcriptomics, and metabolomics. Secondary metabolites were isolated from M. persimmonesis, followed by chemical structure elucidation, PUL gene cluster identification, and RNA sequencing. Pulcherrimin was isolated using 2 M NaOH, its structure was confirmed, and the yield was quantified. Biocontrol efficacy of M. persimmonesis on persimmon fruits and calyx was evaluated by assessing lesion diameter and disease incidence. Following compounds were isolated from M. persimmonesis co-culture with Botrytis cinerea and Fusarium oxysporum: fusaric acid, benzoic acid, benzeneacetic acid, 4-hydroxybenzeneacetic acid, 4-(-2-hydoxyethyl)-benzoic acid, cyclo (Leu-Leu), benzenemethanol, 4-hydroxy-benzaldehide, 2-hydroxy-4-methoxy-benzoic acid, 4-hydroxy-benzoic acid, lumichrome, heptadecanoic acid, and nonadecanoic acid. Exposing M. persimmonesis to different growth media conditions (with or without sugar) resulted in the isolation of five compounds: Tyrosol, Cyclo (Pro-Val), cyclo(L-Pro-L-Tyr), cyclo(Leu-Leu), and cyclo(l-tyrosilylicine). Differentially expressed gene analysis revealed 3264 genes that were significantly expressed (fold change ≥2 and p-value ≤0.05) during M. persimmonesis growth in different media, of which only 270 (8.27%) showed altered expression in all sample combinations with Luria–Bertani Agar as control. Minimal media with ferric ions and tween-80 triggered the most gene expression changes, with the highest levels of PUL gene expression and pulcherrimin yield (262.166 mg/L) among all media treatments. M. persimmonesis also produced a higher amount of pulcherrimin (209.733 mg/L) than Metschnikowia pulcherrima (152.8 mg/L). M. persimmonesis inhibited the growth of Fusarium oxysporum in persimmon fruit and calyx. Toxicity evaluation of M. persimmonesis extracts showed no harmful effects on the liver and mitochondria of zebrafish, and no potential risk of cardiotoxicity in hERG-HEK293 cell lines. Thus, M. persimmonesis can be commercialized as a potent and safe biocontrol agent for preserving food products. •Metschnikowia persimmonesis is an environmentally safe food biocontrol agent.•It produces pulcherrimin, its primary antimicrobial secondary metabolite.•Optimal media for high pulcherrimin yield is minimal media with ferric ions and tween-80.•Toxicity tests revealed no hepatotoxicity, mitochondrial toxicity and cardiotoxicity.